2021
DOI: 10.1094/mpmi-07-21-0180-r
|View full text |Cite
|
Sign up to set email alerts
|

Specialization in a Nitrogen-Fixing Symbiosis: Proteome Differences Between Sinorhizobium medicae Bacteria and Bacteroids

Abstract: Using tandem mass spectrometry (MS/MS), we analyzed the proteome of Sinorhizobium medicae WSM419 growing as free-living cells and in symbiosis with Medicago truncatula. 3215 proteins were identified, over half of the ORFs predicted from the genomic sequence. The abundance of 1361 proteins displayed strong lifestyle bias. 1131 proteins had similar levels in bacteroids and free-living cells, and the low levels of 723 proteins prevented statistically significant assignments. Nitrogenase subunits comprised ~12% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 117 publications
1
3
0
Order By: Relevance
“…Through the comparison of COG functional categories, the DEGs in bacteroids were predominantly involved in amino acid transport and metabolism, clearly consistent with the primary N 2 fixation role of bacteroids in the nodules ( 19 , 20 ). Our present results indicated that the functional classifications of DEGs (either upregulated or downregulated) were very similar in both swollen and nonswollen bacteroids.…”
Section: Discussionsupporting
confidence: 66%
“…Through the comparison of COG functional categories, the DEGs in bacteroids were predominantly involved in amino acid transport and metabolism, clearly consistent with the primary N 2 fixation role of bacteroids in the nodules ( 19 , 20 ). Our present results indicated that the functional classifications of DEGs (either upregulated or downregulated) were very similar in both swollen and nonswollen bacteroids.…”
Section: Discussionsupporting
confidence: 66%
“…The present study confirms our vision that symbiotic Frankia is essentially a nitrogenase machine. Associated proteins were seen here, such as the SuF cluster assembly proteins and the hopanoid biosynthesis proteins (that protect nitrogenase from oxygen), but not the hydrogenase proteins even though they were among those highly expressed [ 33 ]. Frankia hydrogenase proteins seen previously in field nodules [ 21 ] were not detected.…”
Section: Discussionmentioning
confidence: 99%
“…The genomes of strains HO-A22 T and ‘ E. canadensis ’ SHC 2-14 both possess numerous carbon metabolism genes, including those for glycolysis (Embden–Meyerhof pathway), gluconeogenesis, TCA cycle, pentose phosphate and Entner–Doudoroff pathways, which are typical for the members of the Ensifer / Sinorhizobium clade [ 65 , 66 , 67 , 68 , 69 ]. The ‘ E. canadensis ’ SHC 2-14 possessed genes encoding 6-phospho-beta-glucosidase (EC: 3.2.1.86), fructose 1,6-bisphosphate 1-phosphatase (EC: 3.1.3.11), citrate (pro-3S)-lyase beta chain (EC: 4.1.3.6), gluconolactonase (EC: 3.1.1.17), and gluconate dehydratase (EC: 4.2.1.39) that the strain HO-A22 T did not possessed.…”
Section: Resultsmentioning
confidence: 99%
“…The genomes of strains HO-A22 T and 'E. canadensis' SHC 2-14 both possess numerous carbon metabolism genes, including those for glycolysis (Embden-Meyerhof pathway), gluconeogenesis, TCA cycle, pentose phosphate and Entner-Doudoroff pathways, which are typical for the members of the Ensifer/Sinorhizobium clade [65][66][67][68][69]. The 'E.…”
Section: Genomic Analysis and Environmental Implicationsmentioning
confidence: 99%